Rhythm interactive special enablers (R.I.S.E.) – a collaborative community engagement program - Yeoh, Pei Sze; Wen, Fen Beh; Nathaniel, Edwin Lawrance; Swee, Chuan Tan; S. L. Cheah, Kenny; Kuek, Florence; Yiing, Siing Wong (U T S ePRESS (University of Technology Sydney), 2024)
Rhythm Interactive Special Enablers (R.I.S.E.) is a collaborative community engagement program designed to improve motor function, engagement and self- esteem through music- based intervention in children with cerebral palsy (CP). CP is a movement disorder caused by brain damage during development, with spasticity significantly affecting mobility and quality of life. Utilising drum circles, a form of group drumming, R.I.S.E. aims to stimulate neuroplasticity, enhance motor skills and provide a creative and enjoyable therapeutic experience. The program implemented at the Spastic Children’s Association of Selangor & Federal Territory (SCAS&FT) involved 12 biweekly workshops that combined rhythmic exercises and music with the objectives of improving motor coordination, fostering teamwork and boosting participants’ self- confidence. Through structured drum circles, the participants engaged in rhythmic activities that stimulated both cognitive and physical functions. The program was assessed on participant retention, engagement and the incorporation of music into rehabilitation exercises. Feedback from participants and caregivers indicated improvements in motor skills, confidence and community connectedness. Additionally, a ‘Train the Trainer’ initiative was implemented to ensure long-term sustainability, enabling SCAS&FT to autonomously run the program. Moving forward, the program aims to expand to other neurological conditions, ensuring wider accessibility through training and resources.